Anammox co-fungi accompanying denitrifying bacteria are the thieves of the nitrogen cycle in paddy-wheat crop rotated soils - Touqeer Abbas (Environment International, 2019)
Anammox bacteria are the key microbes after denitrifiers in the anaerobic environment. Nitrogen gap cannot be satisfied till date even with the advanced techniques, due to complex microbial network and different pathways. Recently, anaerobic fungi are the concerning point to investigate, which was previously ignored for a long time. Study was conducted with the aim of assessment of an individual and combined contribution of anammox, co-denitrification, and denitrification processes for N losses, under different organic-chemical fertilizers, i.e. 1) control _CK; 2) chemical fertilization _CF; 3) pig manure plus chemical fertilization _PMCF; and 4) straw returned plus chemical fertilization _SRCF). Hybrid techniques of 13C-DNA-Stable isotope and 15N isotopic tracer were used to discriminate the contribution of anammox-co-fungi using antibacterial and antifungal inhibitors. Results showed that fungi are the major culprit in N losses; the overall contribution rate by anammox-co-denitrification was 14.82–29.74%. While in case of individual N losses, fungi were dominating the N losses (3.51–25.60%, AB) than bacteria (7.50–21.80%, AF). The anammox and fungi have a positive correlation with each other's (r = 0.67), principal component analysis (PCA) and correlation analysis validate each other (anammox and fungi), and both showed the same type of attraction to the soil physicochemical properties. However, fungi did not show a significant relationship with NH+4-N (r = 0.38). A clone library of 13C-DNA-SIP was constructed, and results showed that denitrifying fungi were very likely belonges to the genera Agaricus, Aspergillus, Phycomyces, Saitoella, and Trichoderma. Conclusively, we propose that fertilization pattern can change anammox activity and abundance, but fungal activity and community structure undergo changes with organic amendments rather than inorganic fertilizers. Keywords: Anammox, Co-denitrification, DNA-stable isotope, 15N-tracer, Nitrogen cycle